2015
DOI: 10.1016/j.jnutbio.2015.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Extra-virgin olive oil attenuates amyloid-β and tau pathologies in the brains of TgSwDI mice

Abstract: Extra-virgin olive oil (EVOO) is one of the main elements of Mediterranean diet. Several studies have suggested that EVOO has several health promoting effects that could protect from and decrease the risk of Alzheimer’s disease (AD). In this study, we investigated the effect of consumption of EVOO-enriched diet on amyloid- and tau- related pathological alterations that are associated with the progression of AD and cerebral amyloid angiopathy (CAA) in TgSwDI mice. Feeding mice with EVOO-enriched diet for 6 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
70
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 63 publications
5
70
0
1
Order By: Relevance
“…This was associated with a significant decrease in the A β immunoreactivity in the cortex and hippocampus brain regions of the same mice suggesting that A β deposition was significantly affected in the EVOO treated group. When we assessed the proteolytic enzymes and pathways involved in the APP metabolism differently from another report we observed that compared with controls, the treated mice had an increase in α ‐secretase and β ‐secretase and their products, s‐APP α and the sAPP β 11. While that study does not provide data on these two proteases, we think that the discrepancy in the result for the sAPP β could be secondary to the different mouse model implemented by the authors 11.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This was associated with a significant decrease in the A β immunoreactivity in the cortex and hippocampus brain regions of the same mice suggesting that A β deposition was significantly affected in the EVOO treated group. When we assessed the proteolytic enzymes and pathways involved in the APP metabolism differently from another report we observed that compared with controls, the treated mice had an increase in α ‐secretase and β ‐secretase and their products, s‐APP α and the sAPP β 11. While that study does not provide data on these two proteases, we think that the discrepancy in the result for the sAPP β could be secondary to the different mouse model implemented by the authors 11.…”
Section: Discussionmentioning
confidence: 82%
“…When we assessed the proteolytic enzymes and pathways involved in the APP metabolism differently from another report we observed that compared with controls, the treated mice had an increase in α ‐secretase and β ‐secretase and their products, s‐APP α and the sAPP β 11. While that study does not provide data on these two proteases, we think that the discrepancy in the result for the sAPP β could be secondary to the different mouse model implemented by the authors 11. Moreover, by contrast with other reports, we were not able to show any effect of the EVOO on some of the major protein systems in place to control A β clearance and degradation 29.…”
Section: Discussionmentioning
confidence: 82%
“…Recently, several lines of evidence have demonstrated the health effects of extra virgin olive oil (EVOO) and have suggested that its consumption ameliorates age‐related memory decline and decrease the risk of AD onset (Farr et al, ; Feart, Samieri, Alles, & Barberger‐Gateau, ; Pitozzi et al, ). While most of the experimental studies have been focusing on the ability of EVOO to enhance Aβ clearance and reduce its deposition (Abuznait, Qosa, Busnena, El Sayed, & Kaddoumi, ; Qosa et al, ), only fewer research groups have been investigating the tau‐modifying ability of EVOO. On this regard, studies reported that some natural phenolic derivatives from olives, as well as oleocanthal, can prevent tau fibrillization in vitro (Daccache et al, ; Monti, Margarucci, Tosco, Riccio, & Casapullo, ).…”
Section: Introductionmentioning
confidence: 99%
“…From this homogenate, 100 µl were centrifuged at 20,817 x g for 15 min at 4 °C to collect supernatant/lysate that contain soluble Aβ. To measure oligomeric and insoluble Aβ from total brain homogenate, a 2-step serial extraction procedure was used as described previously with modification 62 . In brief, the remained pellet following soluble Aβ extraction was mixed with 2% SDS in PBS containing protease arrest with homogenization, followed by sonication for 10 min and centrifugation at 20,817 x g for 60 min at 22 °C.…”
Section: Analysis Of Aβ Burden In Mice Brainsmentioning
confidence: 99%
“…All brains slices were methanol-fixed and blocked for 30 min with 10% normal donkey serum in PBS. For the detection of Aβ-plaques load, we followed a previously published protocol with slight modification 62 . Briefly, the sections were immuostained with rabbit polyclonal collagen IV antibody (1:200) to detect brain microvessels followed by donkey polyclonal Alexa Flour 647 antibody to rabbit IgG (1:200), which were then incubated in filtered 0.02% thioflavin-S (Thio-S) solution prepared in 70% ethanol for 30 min to detect Aβ deposits.…”
Section: Analysis Of Aβ Burden In Mice Brainsmentioning
confidence: 99%